Analisis Pendapatan Asli Daerah (PAD), Kekayaan Daerah Dan Belanja Modal Dalam Meningkatkan Kemandirian Keuangan Pemerintah Kota Metro - Hadijah, Umi; Zanaria, Yulita; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2025)
This research aims to analyze local original income, regional wealth and capital expenditure in increasing the financial independence of metro city governments. This type of research uses qualitative research with a descriptive approach. The researcher is the main instrument of this research, assisted by data from the 2020-2023 metro city regional government financial reports. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of this research show that local original income, regional wealth and capital expenditure have not been able to increase the financial independence of metro city governments.